EKSPANSI PERKEBUNAN KELAPA SAWIT DI KALIMANTAN TENGAH: MEKANISME POLITIK DI BALIK KERUSAKAN EKOLOGI - Katriani Puspita Ayu (Prodi Sosiologi FISIP UPR, 2021)
The expansion of palm oil plantations creates various ecological problems in Central Kalimantan. Despite the fact that palm oil opening caused ecological damage, the mechanism behind palm oil expansion is vital to discuss. This study tries to identify the area expansion and investigate the political mechanism of palm oil development in Central Kalimantan. This research uses various literatures, articles and archives, which is organized and analysed to answer the research questions. The result shows that negative environmental impacts such as: forest loss, water pollutant, soil erosion, biodiversity loss and greenhouse gas emission occurred within the expansion of palm oil area. All ecological consequences are indirectly caused by the ‘concession-trade’ mechanism which exist in every level of authority. Competition among level of government in permit awarding has been the significant driver for palm oil expansion. Head of district that grants permit without regard to procedures and regulations has trade the permit for support in Pilkada campaign. Clientelism and patrons’ relation between the palm oil company and district authority becomes the reason of palm oil expansion and contribute to the environment issues in Central Kalimantan.